A qualitative study of markers' perceptions on onscreen marking in five subject areas. Issue 7 (17th November 2017) - Yang, Min; Yan, Zi; Coniam, David
ABSTRACT: This paper reports on a qualitative study on markers' perceptions of onscreen marking (OSM) in association with key influential factors of marking reliability. The study has made adaptations to an existing framework proposed by Black, Suto, and Bramley in 2011 for exploring issues related to influential factors of marking reliability in OSM contexts. Specifically, the study investigated those influential factors in the framework that can be manipulated and managed by the examination authority. The study involved 31 markers for a large-scale publication examination who were secondary school teachers from 5 subject areas. The major themes indicated that markers' attitudes towards OSM might be potentially associated with the types of questions they marked. Further, the advantages and disadvantages of OSM as perceived by the markers were likely to be related to key influential factors of reliability pertaining to the quality control process and the usability of technology in the OSM system.